Uncovering Rural Employee Performance through Insights from Indonesia: Mengungkap Kinerja Karyawan Pedesaan melalui Wawasan dari Indonesia - Maulana Bagas Alfansyah; Hasan Ubaidillah (Academia Open, 2024)
This study examines the impact of work environment, leadership, and compensation on the performance of office employees in Karang Jati Village, Kec. Pandaan District, Pasuruan. Using a quantitative associative approach, data were collected from 52 village officials through a census sampling technique and analyzed with SPSS version 22. The results indicate that work environment, leadership, and compensation each have a positive and significant effect on employee performance. These findings underscore the importance of enhancing workplace conditions, leadership quality, and compensation to improve employee performance in village offices. Future research should explore additional factors and larger samples for broader insights. Highlights: 1. Positive impact of work environment, leadership, and compensation on performance.2. Census sampling of 52 village officials.3. Improve workplace, leadership, and compensation to boost performance. Keywords: Employee Performance, Work Environment, Leadership, Compensation, Village Officials